The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.carrev.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and performance of the orbital atherectomy system for treating calcified coronary artery lesions: 5-Year follow-up in the ORBIT I trial

Abstract: The ORBIT I trial suggests that OAS treatment continues to offer a safe and effective method to change compliance of calcified coronary lesions to facilitate optimal stent placement in these difficult-to-treat patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
0
31
0
1
Order By: Relevance
“…Similarly, abrupt closure occurred in Table 4. Univariate analysis of factors influencing the incidence of major adverse cardiac events (MACE) and major cardiac and cerebrovascular events (MACCE) after rotational atherectomy procedure CABG -coronary artery bypass grafting; CI -confidence interval; COPD -chronic obstructive pulmonary disease; DAPT -dual antiplatelet therapy; GFR -glomerular filtration rate; HR -hazard ratio; IVUs -intravascular ultrasound; LVEF -left ventricular ejection fraction; OACoral anticoagulation; PCI -percutaneous coronary intervention; RCA -right coronary artery; TIA -transient ischaemic attack 0.9% of individuals after the use of OA, and in 1.8%, after the procedure, compared with rates from 1% to 4% from other studies that reported abrupt closure during RA [11,12]. Perforations occurred in 0.9% of patients after the use of OA and in 1.8% after the procedure, compared with 0.4% to 2.5% in RA studies reporting on this complication [15].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, abrupt closure occurred in Table 4. Univariate analysis of factors influencing the incidence of major adverse cardiac events (MACE) and major cardiac and cerebrovascular events (MACCE) after rotational atherectomy procedure CABG -coronary artery bypass grafting; CI -confidence interval; COPD -chronic obstructive pulmonary disease; DAPT -dual antiplatelet therapy; GFR -glomerular filtration rate; HR -hazard ratio; IVUs -intravascular ultrasound; LVEF -left ventricular ejection fraction; OACoral anticoagulation; PCI -percutaneous coronary intervention; RCA -right coronary artery; TIA -transient ischaemic attack 0.9% of individuals after the use of OA, and in 1.8%, after the procedure, compared with rates from 1% to 4% from other studies that reported abrupt closure during RA [11,12]. Perforations occurred in 0.9% of patients after the use of OA and in 1.8% after the procedure, compared with 0.4% to 2.5% in RA studies reporting on this complication [15].…”
Section: Discussionmentioning
confidence: 94%
“…Treatment of challenging calcified lesions often leads to increased MACE rates. The ORBIT II trial reported the successful stent delivery in 97.7% of the included patients and residual stenosis < 50% in 98.6% with a low angiographic complication rate [11,12]. The incidence of slow-flow and no-reflow was notably very low, occurring in < 1% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 33 subjects, the observed MACE rate at 2 years was 15 % (5/33), 3 years was 18 % (6/33) and 5 years 21 % (7/33). 23,24 The ORBIT II trial was a prospective, single-arm multicentre, non-blinded clinical trial that enrolled 443 consecutive patients with severely calcified vessel revascularisation (0.7 %) were reported. The incidence of slow flow or no reflow in the rotational atherectomy has been reported to be 6 % to 15 %, 25,26 whereas in the ORBIT II trial the rate of persistent slow flow/no reflow for orbital atherectomy were notably very low, occurring in 0.9 % of patients.…”
Section: Clinical Evaluation For Coronary Orbital Atherectomy Systemmentioning
confidence: 99%
“…Recent studies have suggested that early phase neointimal hypertrophy is in part due to calcification. These lesions are more robust and may contribute to stent under expansion if treated with balloon angioplasty alone [1, 2]. The management of ISR is complex, with a few treatment modalities recognized other than the balloon angioplasty and further stent placement.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, implementation of these techniques can be ineffective in the presence of heavily calcified lesions. Calcified lesions are challenging as they can be associated with increased rates of stent restenosis due to being under expansion and poor apposition, which predispose to luminal loss and worse clinical outcome [1, 3]. OAS was recently introduced to the US market for the management of heavily calcified coronary lesions.…”
Section: Introductionmentioning
confidence: 99%